Chinook salmon (Oncorhynchus tshawytscha) genome and transcriptome - Christensen, Kris A. (PLoS One, 2018)
When unifying genomic resources among studies and comparing data between species, there is often no better resource than a genome sequence. Having a reference genome for the Chinook salmon (Oncorhynchus tshawytscha) will enable the extensive genomic resources available for Pacific salmon, Atlantic salmon, and rainbow trout to be leveraged when asking questions related to the Chinook salmon. The Chinook salmon’s wide distribution, long cultural impact, evolutionary history, substantial hatchery production, and recent wild-population decline make it an important research species. In this study, we sequenced and assembled the genome of a Chilliwack River Hatchery female Chinook salmon (gynogenetic and homozygous at all loci). With a reference genome sequence, new questions can be asked about the nature of this species, and its role in a rapidly changing world.